Dietary and environmental modulation for the gut environment: yogurt promotes microbial diversity while chloride hot springs improve defecation status in healthy adults - Choi, Jungmi; Takeda, Midori; Managi, Shunsuke (Frontiers in Nutrition, 2025)
The gut microbiome plays a central role in human health and can be shaped by both dietary and environmental factors. While yogurt has been widely studied for its ability to modulate the gut microbiota as a dietary factor, the effects of chloride hot spring bathing as an environmental factor remain largely unexplored. This randomized, controlled trial investigated the individual and combined effects of yogurt consumption and chloride hot spring bathing on gut microbiota, fecal metabolites, and defecation function in healthy adults. 47 participants (39 eligible participants + 8 additional recruits) were randomly assigned to one of three groups: control, yogurt only, or yogurt plus hot spring bathing. Over a four-week period, participants in the yogurt groups consumed 180 g of yogurt daily, and those in the hot spring group additionally bathed in a chloride-rich hot spring at least every 2 days. Fecal samples and defecation status questionnaires were collected before and after the intervention. Gut microbiota profiles were analyzed using 16S rRNA gene sequencing, and short-chain fatty acids (SCFAs) were measured by gas chromatography–mass spectrometry (GC–MS). Yogurt consumption significantly increased gut microbial diversity, as shown by higher Shannon index, observed ASVs, and Faith’s phylogenetic diversity, with notable enrichment of beneficial taxa such as Akkermansia. A significant reduction in formic acid levels was also observed in the yogurt group, while overall SCFA profiles remained unchanged. Although no significant microbiota or metabolite shifts were detected in the yogurt + hot spring group, it showed the greatest numerical improvement in defecation scores. These findings suggest that accessible lifestyle interventions, such as dietary modification and hot spring bathing, can positively influence gut health and may serve as practical strategies for promoting overall well-being.